O artista, o ciclista e o peão : a obra de Jonas Barros - Rodrigues, Alessandra Cristina (2016)
The visual arts in the state of Mato Grosso, contributed to the creation of a regional identity, as they reproduced plenty of local nature icons such as jabiru storks, macaws, jaguars, alligators, oxen, fish and other entities of the fauna and flora. In this context, in 1986, Jonas Barros emerged participating in the "X Hall of Young Mato Grosso Art" and making his way in the world of fine arts. Jonas Barros, the artist, is also a cowboy and a cyclist. Such personal experience, in transit between rural life and urban, is the foundation of his work. From the farm rivers he brings to his paints water, fish, rocks and leaves, taking thus the built regional iconography and winning the popular nickname "fish painter". An self-taught artist in his studies and trials for the development of his own work, Barros achieve diversity in both thematically and in material supports and although from the riverbeds in a figurative painting, we can also include creations like sculptures, objects, drawings, murals, paintings abstract, photos, etc. Our goal in this work is the investigation of his work and in order to achieve it, we contextualize the artist historically with the support of selected images, we address some of his biography and we enter in his artistic production discussing career, awards received, events attended and works produced. For this task we lay hold of literature with emphasis in the areas of aesthetics, art history and Mato Grosso plastic arts. We rely fundamentally on texts and ideas, Luigi Pareyson, John Berger, Aline Figueiredo, Suzana Guimarães, Gilles Deleuze and Jonas Barros himself. We also engage in the analysis and critique of both the theory studied as the very work of Jonas Barros, always with the interviews allowance granted by the artist.